Computational Modeling of Flow in an in Vitro Cerebrovascular Model Under Pulsatile Conditions with Experimental Validation - Boyang Su; Brent A. Craven; Cody J. Kubicki; Daniel Khalil; Scott D. Simon; Keefe B. Manning (Cardiovascular Engineering and Technology, 2026)
Purpose Computational fluid dynamics (CFD) has been widely used to understand various cardiovascular diseases such as acute ischemic stroke (AIS), which occurs when a blood clot lodges in the cerebrovasculature and obstructs blood flow that may lead to brain damage or death. Compared with medical imaging, CFD can predict hemodynamics and clot migration, which are crucial in better understanding the biomechanics of AIS. To rely on computational modeling, however, the simulations need to be validated by comparing with experiments Methods In this study, we develop an in vitro experimental model of pulsatile flow in the aorta and cerebrovasculature. The model was filled with a blood analog fluid and pulsatile flow was driven by a piston pump to generate realistic physiological flow conditions. Experimental measurements of the time-varying pressure and flow rate were acquired and are used to validate corresponding CFD simulations Results CFD predictions of the time-averaged pressure at the outlets are shown to be within 8% of the experimental measurements, while the time-averaged flow rate is within 1%. Conclusions This work demonstrates a promising capability for modeling embolus migration and lodging in the brain. Future work will validate simulations of clot migration that may be used to better understand AIS biomechanics and treatment options.